KONSEP INSAN KAMIL DALAM KURIKULUM PAI - Ghozali, Solchan; pengelola, pengelola (LPPM STAI Ihyaul Ulum Gresik, 2025)
The Islamic Religious Education (PAI) curriculum for Senior High Schools (SMU) was designed with the primary goal of enabling students to understand Islamic teachings comprehensively, encompassing aspects of faith (‘aqidah), ethics (akhlaq), and Islamic law (shari’ah). Upon further analysis, the objectives of this curriculum reveal both similarities and differences with the concept of insān kāmil as articulated by Al-Ghazali. According to Al-Ghazali, insān kāmil refers to an individual who possesses noble character, upholds moral values, refrains from sinful acts, and actively engages in promoting good and preventing evil (amar ma'ruf nahi munkar). Essentially, the objectives of the 2006 PAI curriculum align with Al-Ghazali’s vision of insān kāmil, aiming to shape students into morally and spiritually excellent individuals. The key difference lies in the concepts of al-muḥtasib and mu’min al-ḥisbah, in which Al-Ghazali emphasizes individual awareness as an active moral overseer within society. Based on this background, the main research problems can be formulated as follows: 1) What is the concept of insān kāmil according to Al-Ghazali? 2) How do the objectives of the 2006 SMU PAI curriculum align with the concept of insān kāmil as defined by Al-Ghazali? This study falls under the category of qualitative research, an approach aimed at producing descriptive data in the form of written or spoken narratives from individuals and observed behaviors. The study was conducted through a library research approach. Data collection was carried out using documentation techniques, involving the examination and recording of various written sources relevant to the research focus. The analysis technique employed was content analysis, aimed at deriving meaning and drawing conclusions from the literature and documents used as data sources. Based on the researcher’s findings, the 2006 PAI curriculum remains closely related to Al-Ghazali’s thought. This is evident in its emphasis on encouraging students to worship Allah sincerely and to avoid reprehensible traits such as hypocrisy (riya’), arrogance, breach of promises, and dishonesty. Through this educational process, students are expected to develop akhlaq karimah (noble character) as the foundational basis for shaping a holistic Muslim personality.